Terfezia lusitanica, a new mycorrhizal species associated to Tuberaria guttata (Cistaceae) - Bordallo, Juan-Julián; Rodríguez, Antonio; Santos-Silva, Celeste; Louro, Rogério; Muñoz-Mohedano, Justo; Morte, Asunción (Phytotaxa, 2018)
A new Terfezia species associated with Tuberaria guttata, Terfezia lusitanica sp. nov., is described from Spain and Portugal. This claim it’s based on the specimen’s distinct morphology and unique ITS-rDNA sequence. Macro and micro descriptions and phylogenetic analyses of ITS data are provided for T. lusitanica and discussed in relation to similar spiny-spored Terfezia species. T. lusitanica differs morphologically from other spiny-spored Terfezia, that share the same habitat, by the combination of its ochre peridium colour and spores size, and in its ITS nrDNA sequence from all other ITS sequenced Terfezia species. Among the morphologically similar species, T. fanfani has a reddish peridium, T. extremadurensis has distinctly larger spores and tuber-like gleba, and T. cistophila has smaller spores, a spermatic odour, and is never found in association with T. guttata.